2012
DOI: 10.1364/ao.51.001532
|View full text |Cite
|
Sign up to set email alerts
|

Fast response varifocal lenses using KTa1−xNbxO3 crystals and a simulation method with electrostrictive calculations

Abstract: We fabricated cylindrical varifocal lenses with fast responses by using the strong Kerr effect of KTa(1-x)Nb(x)O(3) (KTN) single crystals. We observed focus shifts of up to 87 mm with the assistance of a 250 mm focal length lens, which corresponds to a focus shift from infinity to 720 mm by the KTN lens itself. The response time was as fast as 1 μs. We also present a simulation method for calculating refractive index distributions in KTN single crystals, which is essential when designing the lens. The method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The huge EO effect makes it possible to realize quick and strong control of the refractive index in the KTN crystal by employing electrical signals. We have already confirmed that the KTN lens works properly as a fast response varifocal lens [8]. The KTN lens is especially effective in situations where a transmitted beam is linearly polarized parallel to the direction of an applied electric field.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The huge EO effect makes it possible to realize quick and strong control of the refractive index in the KTN crystal by employing electrical signals. We have already confirmed that the KTN lens works properly as a fast response varifocal lens [8]. The KTN lens is especially effective in situations where a transmitted beam is linearly polarized parallel to the direction of an applied electric field.…”
supporting
confidence: 60%
“…(1) [8]. Figure 2(b) shows the calculated optical path distribution, which depends on the y coordinate of the KTN lens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact the strain components must be calculated by regarding the KTN block as an elastic substance strained by the electrostrictive stress as a driving force so that the strain components minimize the total free energy of the block. [6] To calculate the electrostrictive stress, we used the same spatial distributions of E x and E z as those used for Fig. 8.…”
Section: Polarization Independencementioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] KTN crystal, a perovskite-type oxide material, well recognized for its excellent EO performance where the index modulation is proportional to the square of the electric field, can realize rapid response, strong control of the refractive index and much lower driving energy comparing to LiNbO 3 for the same change ∆n in the refractive index. For this reason, KTN-based single crystal has been considered as promising materials, and has then been substantially investigated and successfully exploited in such diverse areas as EO deflection, [6][7][8] EO scanner, 9 a fast varifocal lens [10][11][12][13] and so on. 14,16,17 Mn:Fe:KTN crystal doped with both iron and manganese simultaneously are of particular interest because of its two competing subsystems of dipole moments and exhibits faster EO response than single-doped crystal.…”
Section: Introductionmentioning
confidence: 99%